Bidirectional longitudinal associations between estimated muscle mass and self-reported chronic lung disease in middle-aged and older adults: findings from the China health and retirement longitudinal study - Jing Yang; Weixia Li; Ruixuan Zhao; Jingjing Lu; Xinlu Cui; Jianlin Lin; Li Cao (BMC Public Health)
Abstract Background The bidirectional relationship between muscle mass and chronic lung diseases (CLD) in middle-aged and older adults remains inadequately explored. This study aims to investigate the bidirectional association between estimated muscle mass and self-reported chronic lung diseases while elucidating the mediating mechanisms underlying this relationship. Methods This study utilized data from the nationally representative China Health and Retirement Longitudinal Study (2011–2018), focusing on individuals aged 45 years or older. Cox regression was used to investigate the bidirectional relationship between estimated muscle mass and self-reported CLD. Causal mediation analysis was employed to evaluate the role of 16 blood biomarkers as potential mediators. Sensitivity analysis using cross-lagged models was conducted to verify the robustness of the bidirectional association between estimated muscle mass and self-reported CLD. Results Among 10,591 participants, 1,742 (16%) self-reported CLD during a median follow-up of 4.4 years. Participants with low estimated muscle mass had a 27% higher risk of developing self-reported CLD compared to those with normal muscle mass (HR = 1.27, 95% CI: 1.12–1.44). In a separate analysis of 6,067 participants, 708 (12%) experienced new-onset estimated low muscle mass, with those reporting CLD showing a 26% increased risk of muscle loss during a median follow-up of 2.5 years (HR = 1.26, 95% CI: 1.06–1.49). Notably, individuals with insufficient physical activity exhibited a significantly higher risk of self-reported CLD compared to those who engaged in regular exercise (HR = 1.91; 95% CI: 1.37–2.66). Additionally, the negative impact of low estimated muscle mass was more pronounced in male participants than in females (HR = 1.65; 95% CI: 1.33–2.03) over the same follow-up period. Causal mediation analysis suggested that cystatin C may mediate 0.61% of the association between estimated muscle mass and self-reported CLD. Conclusion There is a bidirectional relationship between self-reported CLD and low estimated muscle mass. Self-reported CLD may cause varying degrees of estimated muscle mass reduction across different population subgroups. Understanding this dynamic and its variations can enhance prevention and treatment strategies for both conditions.